I Left Venus and Came Back to Mars: Temporal Focus Congruence in Dyadic Relationships Following Maternity Leave - Freeney, Yseult; van der Werff, Lisa; Collings, David G. (Organization Science, 2022)
Temporal focus on past, present, and future of contributions to work is critical to understanding how employees and their line managers navigate career disruptions and minimize their potential for negative impact. This paper reframes temporal focus using a dyadic, relational perspective to explore how temporal focus (in)congruence shapes resocialization experiences for returners and their line managers following maternity leave disruption. Our qualitative study draws on 54 interviews across 27 organizations and demonstrates that a congruent, broader temporal focus—that embraces the past, present, and future—is associated with more positive relational and career outcomes than an incongruent focus, where one dyadic partner holds a narrow temporal focus. Our findings explicate how the adoption of a broad versus narrow temporal focus creates a perception of maternity leave as either a brief interlude or a major disruption. A congruent, broader temporal focus allows returners and their line managers to reduce their reliance on typical motherhood biases and instead, consider the woman’s past, present, and potential future contributions over the course of her career. We highlight the importance of temporal focus congruence at a dyadic level and the value of adopting a broader temporal focus on careers while offering new insights regarding the temporal dynamics inherent to maternity leave transitions for both returners and their managers.